2012
DOI: 10.1590/s0036-46652012000400002
|View full text |Cite
|
Sign up to set email alerts
|

Antibody levels to hantavirus in inhabitants of western Santa Catarina State, Brazil

Abstract: SUMMARYHantavirus cardiopulmonary syndrome (HCPS) is an infectious disease caused by hantaviruses of the family Bunyaviridae, and is transmitted by aerosols of excreta of infected rodents. The aim of the present study was to determine antibody levels to hantavirus in the population that lives at frontier of Brazil and Argentina. Participated of the study 405 individuals living in the municipalities of Bandeirante, Santa Helena, Princesa and Tunapolis, state of Santa Catarina, Brazil. IgG antibodies to hantavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(39 reference statements)
0
4
1
3
Order By: Relevance
“…The seroprevalence of anti-hantavirus IgG antibodies detected in this study is higher than that reported in the serological survey conducted by Souza et al 10 Despite using similar techniques, they observed 1.97% seroprevalence in the samples from the urban and rural areas of four municipalities of the Santa Catarina State. In another study conducted in cities near the border between Brazil and Argentina, still in the State of Santa Catarina, they found a 3.5% seroprevalence 11 .…”
contrasting
confidence: 87%
“…The seroprevalence of anti-hantavirus IgG antibodies detected in this study is higher than that reported in the serological survey conducted by Souza et al 10 Despite using similar techniques, they observed 1.97% seroprevalence in the samples from the urban and rural areas of four municipalities of the Santa Catarina State. In another study conducted in cities near the border between Brazil and Argentina, still in the State of Santa Catarina, they found a 3.5% seroprevalence 11 .…”
contrasting
confidence: 87%
“…Considering that blood donors are commonly local inhabitants, it is possible that hantaviruses are circulating across practically all of the state. Of note, a study including 340 individuals inhabiting two cities in the western border of the state of Santa Catarina with Argentina, found 3.5% of individuals to be seropositive for hantavirus 7 . It might be worth noting that hantavirus infection is usually acquired by contact with wild rodents, often in the rural areas, and not in the urban environment.…”
Section: Resultsmentioning
confidence: 99%
“…Cases of hantaviruses in Minas Gerais State have been described since 1998, and the Southeastern region of the state accumulates most of the cases 3,4 . Several serological studies conducted in the country have presented evidence of hantavirus circulation in different human populations in the absence of reported HPS 2,[4][5][6][7][8][9] . This suggests the possibility of silent virus transmission and consequently an underestimation of the virus's spatial distribution.…”
mentioning
confidence: 99%
“…Such activities are usually not related to planting and harvesting, camping, or hunting, which are known risk factors for acquiring Hantavirus infections [7][8][9] .…”
mentioning
confidence: 99%